PERKEMBANGAN NILAI BUDAYA KESENIAN RANTAK KUDO SEBAGAI WARISAN BUDAYA KERINCI - ediantes, ediantes (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
The development of Rantak Kudo Art is a performing arts phenomenon that occurs in the Kerinci area, in this dance performance is not performed specifically by the dancers, but is danced by the local community who mingle with each other while accompanying music produced from single organ and traditional musical instruments such as flutes and drums. Another unique thing is that this dance is performed all night, meaning that the dance participants are able to dance for more than 6 hours continuously, so that people think that Rantak Kudo dancing is accompanied by magical elements in the performance. At this time the art in the form of mass dances was present at every traditional art activity and event, although it was alleged that the Rantak Kudo art was influenced by the Rantak Kudo dance that developed in the South Coast and also the Rantak Kudo dance from the Rawang area. In particular, this study aims to reveal the forms and cultural values of Rantak Kudo art in the Kerinci area. The research methodology used in this study is post-positivism qualitative research, which is a method that not only analyzes the appearance, but also uses statistical methods and documents as a means to place groups of subjects into a larger population. The results of this study can be grouped into several points, including the cultural form of Rantak Kudo art, the cultural values contained in the Rantak Kudo art, the economic value, the value of art and creativity, and the value of the interpretation of ideas.